2008
DOI: 10.1177/0890334408322265
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Practices in Duzce, Turkey

Abstract: Exclusive breastfeeding among infants less than or equal to 6 months old and continued breastfeeding (20-23 months) are high-priority indicators of infant health. We aimed to assess breastfeeding practices, using standardized breastfeeding indicators, and to determine the causes of early discontinuation of breastfeeding (< or = 6 months) in children aged 0 to 24 months in Duzce, Turkey. In this cross-sectional study, the study group consisted of 158 children, and questionnaires were completed by face-to-face i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 4 publications
3
23
1
2
Order By: Relevance
“…In total, 72% of the mothers breastfed their newborns in the first six hours after baby's birth This finding is in line with previous studies in Timor Leste, India, and Turkey [16-18]. However, 28% of the Nias mothers initiated breastfeeding six hours after birth or even later, and 17% discarded the colostrum due to local traditional beliefs similar to the ones in the study in India [19,20].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In total, 72% of the mothers breastfed their newborns in the first six hours after baby's birth This finding is in line with previous studies in Timor Leste, India, and Turkey [16-18]. However, 28% of the Nias mothers initiated breastfeeding six hours after birth or even later, and 17% discarded the colostrum due to local traditional beliefs similar to the ones in the study in India [19,20].…”
Section: Discussionsupporting
confidence: 86%
“…This low prevalence of exclusive breastfeeding has been commonly reported in studies in India, Bangladesh, Sri Lanka, Turkey, and Tanzania [18,20,23,24,30]. Based on qualitative assessment, the most common barrier to practicing exclusive breastfeeding in the study area was perceived insufficient breast milk production ( n = 30).…”
Section: Discussionmentioning
confidence: 71%
“…It was thus surprising that doctors’ recommendations were among the most important reasons to stop exclusive breastfeeding, since the physiological and psychological beneficial effects of breastfeeding should be well acknowledged by them. Similar influences by physicians have been reported in a study in Turkey [11]. A study in Puerto Rico showed that as many as 26% of primary care physicians did not encourage exclusive breastfeeding [12].…”
Section: Discussionsupporting
confidence: 66%
“…The timely initiation rates are higher in other countries such as United States where 73% achieved this and in Turkey where 62% achieved this. [10,25] This may be as a result of better and more efficient health facilities in these regions. A study conducted in Sokoto State, Nigeria, reported that only 8% of the respondents initiated breastfeeding within an hour of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Another study in Turkey however reported an exclusive breastfeeding rate of 22.4%. [10] This shows that the large disparities in exclusive breastfeeding rates are not limited to Nigeria. The findings also show that it is possible to attain those desired high exclusive breastfeeding rates and are a call to action for countries like Nigeria to ensure there is widespread dissemination of appropriate health education and provision of support structures such as crèches to encourage women to exclusively breastfeed their infants for the first six months of life.…”
Section: Discussionmentioning
confidence: 99%